Comparison of Knowledge and Practices among University Students of Allied Health Sciences and Engineering Departments in University of Lahore, Pakistan about Corona Virus Disease - Iqra Fatima, Seema Shafeeq, Jawaria Sultan, Fatima Zubair, Fatima Arshad, Ahmed Majeed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Corona Viruses is a group of viruses that cause diseases in both humans and mammals and are known to cause chronic respiratory diseases. The viruses among them include SARS, MERS and COVID-19. The most recent pandemic was a result of COVID-19. Older people and those with underlying medical problems are more likely to develop serious illness. Objective: To compare the knowledge and practices of Allied Health and Engineering students of the University of Lahore about Corona Virus Disease. Methodology: A cross-sectional questionnaire based survey was conducted on 326 students studying in Allied health Sciences and Engineering departments of UOL. The data was compiled in SPSS, version 24 for analysis. Results: The students of Allied Health Sciences had a better understanding and were more aware of COVID-19, its percussions and the methods to prevent its spread than of the Engineering Students. More than half of the Engineering students have found to have less understanding about the causative agent of the COVID-19 and similar trend was found in other categories. Health sciences students showed higher tendency towards hands hygiene practices than engineering students. Practical implication: Lessons learned from different outbreaks of infectious diseases suggested that knowledge and practices towards infectious diseases are associated with level of panic emotion among the population, which can further complicate attempts to prevent the spread of the disease. To facilitate outbreak management of COVID-19 in Lahore, Pakistan, there is an urgent need to understand the public's awareness of COVID-19. Keeping these considerations in mind this research was kicked-off to gauge the knowledge and practices of these medical and engineering students about Corona virus disease. Conclusion: The study shows that educational background plays a vital role in disease control and it will help in successful uptake of control interventions for prevention of COVID-19. Keywords: COVID-19, Engineering, Allied Health Sciences, knowledge, practices, comparative analysis